Analisis Deskriptif Standard Kepemimpinan Small business Suzuki Magetan - Zulin Nurchayati (Universitas Merdeka Madiun, 2019)
In general, small business leadership in Indonesia adheres to traditional leadership or traditional. The object of this research is Suzuki Magetan's small business leadership in Suzuki's automotive sales, repair and maintenance services, which is based on the Suzuki Leadership Standards combined with traditional leadership. This study used descriptive qualitative method. Data obtained through participant observation where the researcher is involved with daily activities of the data source. Suzuki Magetan small business leadership standards based on the Suzuki Leadership Standards and traditional leadership, namely: making a written job description, making a plan of target work (goal setting), data analysis, action plan, following training in communication skills, business English, ESQ leadership, seminars, etc. Result oriented by looking at process oriented using PDCA circulation (Plan, Do, Check, Action).